Study Of Legal Positivism - Yogi Prasetyo; Absori Absori (UIN Sunan Kalijaga Yogyakarta, 2019)
This article is a result of study that aims to explain the importance of the thought of legal positivism. The rapid development of science and technology can cause problems in life. The demands of the necessities of life to be fulfilled by human beings. Therefore, the development of legal positivism as a legal discipline closely related to the rational method of legal thinking becomes very important. There are various issues that require assertiveness and legal certainty to solve them. Understand how laws in legislation are important in law science, because law embraces the principle of legality in the system of state positive law norms. The study method used is literature with philosophical approach. From the results of the study shows that the study of legal positivism is very important to understand the law in writing in the legislation. Deductive that became characteristic in the method of reasoning legal positivism to get a correct understanding of the law of the general provisions established in the legislation. Rational-based legal positivism is very useful to establish the degree of legal certainty.